THE DEVELOPMENT METHODS OF THE SECURITY DOCUMENT WHAT ARE BASED ON LATENT ELEMENTS WITH FRACTALS - Назаркевич, Марія Андріївна; Дронюк, Іванна Мирослаівна; Троян, Оксана Анатоліївна; Томащук, Тетяна Юріївна (Ukrainian Information Security Research Journal, 2015)
In information security plays an important role state pro-tection of printed documents. This work is devoted to the development of latent element what based on fractals. There are special graphic construction based on which a latent elements that increase the efficiency and reliability of protection. In constructing graphical elements on the basis of fractal geometry formed complex pattern of hid-den information. Graphic elements formed based on fractal provide complexity play a protective element, and information that is latent, can be played only by well-known designers template.